Cardiac Mast Cells: A Two-Head Regulator in Cardiac Homeostasis and Pathogenesis Following Injury - Jin, Jing; Jiang, Yuanyuan; Chakrabarti, Subrata; Su, Zhaoliang (Frontiers in Immunology, 2022)
Cardiac mast cells (CMCs) are multifarious immune cells with complex roles both in cardiac physiological and pathological conditions, especially in cardiac fibrosis. Little is known about the physiological importance of CMCs in cardiac homeostasis and inflammatory process. Therefore, the present review will summarize the recent progress of CMCs on origin, development and replenishment in the heart, including their effects on cardiac development, function and ageing under physiological conditions as well as the roles of CMCs in inflammatory progression and resolution. The present review will shed a light on scientists to understand cardioimmunology and to develop immune treatments targeting on CMCs following cardiac injury.